Clinical, Etiologic And Evolutionary Characterization of Osteoarticular Infections in Children Hospitalized in A Referral Tropical Medicine Center - Sanabria, Gabriela; Navarro, Andrés; Araya, Soraya; Arbo, Antonio (Journal of Medical Biomedical and Applied Sciences, 2019)
Introduction: Osteoarticular infections (OAI) are an infectious pediatric pathology, generally of bacterial etiology, relatively frequent and potentially severe. Objective: To determine the clinical, etiological and evolutionary characteristics of osteoarticular infections in hospitalized children in a referral center. Materials and methods: Observational, retrospective cross-sectional study. We reviewed the medical records of all children from 1 month to 15 years of age hospitalized in the Pediatric Service of the Institute of Tropical Medicine (IMT) from 01/01/2010 to 12/31/2015 with diagnosis of osteomyelitis, Osteoarthritis or Septic Arthritis Results: A total of 59 children with an OAI diagnosis were hospitalized. 25 (42.4%) diagnosed with septic arthritis, 6 (10.2 %) polyatritis, 21 (35.6 %) osteomyelitis and 7 (11.9 %) osteoarthritis. The mean age was 8.9 + 3.8 years, 40 (67.8 %) were males. Pain and functional impotence were the most frequent symptoms. 47 (79.6%) were located in lower limbs. Staphylococcus aureus methicillin resistant (MRSA) 17 (41.5 %), methicillin sensitive Staphylococcus aureus (SAMS) 18 (43.9 %), Pseudomonas sp. 2 (4,9 %), Klebsiella pneumoniae BLEE 3 (7.3 %), another 5 (12,1 %). In this series 2 patients diagnosed with septic shock at the joint point (Hip and knee respectively) without germ isolation died. Conclusion: OAI remains to be pathology of high morbidity in our environment. They affect more often the lower limbs as well as school-age male children. The UAA was the most frequent isolated germ. The mortality rate is low and the sequelae continue to appear.